2009
DOI: 10.2983/035.028.0415
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of the Eastern OysterCrassostrea virginica(Gmelin, 1791) in the Gulf of Mexico

Abstract: Genetic variation in eastern oysters (Crassostrea virginica) collected from 13 sites in the Gulf of Mexico was examined using a combination of mitochondrial DNA (mtDNA) sequencing, mtDNA restriction fragment length polymorphism analysis, and nuclear single nucleotide polymorphism analysis. Both mitochondrial and nuclear markers showed significant differentiation among samples. Combined with previous allozyme and microsatellite data, these results indicate considerable population subdivision throughout the Gulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
4
30
1
Order By: Relevance
“…Several studies have shown that a hindrance to gene flow exists between the western and eastern Mediterranean, even for species with high dispersal capabilities and large population sizes (e.g., [65], [66], [67]). This result was partially consistent with findings reported for other bivalves with a high potential for dispersal, along with significant genetic differentiation and a pattern of isolation by distance (e.g., [68], [69], [70]). …”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that a hindrance to gene flow exists between the western and eastern Mediterranean, even for species with high dispersal capabilities and large population sizes (e.g., [65], [66], [67]). This result was partially consistent with findings reported for other bivalves with a high potential for dispersal, along with significant genetic differentiation and a pattern of isolation by distance (e.g., [68], [69], [70]). …”
Section: Discussionsupporting
confidence: 91%
“…Some intraspecific genetic differences have been observed in Crassostrea rhizophorae from the Caribbean (Hedgecock & Okazaki 1984) and between Atlantic and Gulf of Mexico C. virginica (Hare & Avise 1998, Varney et al 2009). As the larvae of Crassostrea are planktonic and have great dispersal capability (for instance, C. virginica larvae can spend 2 to 3 wk in the plankton; Kennedy 1996), the high levels of genetic differentiation found in these works and in the present study are surprising.…”
Section: Geographical Distribution Isolation By Distance and Histormentioning
confidence: 99%
“…While highly polymorphic markers such as microsatellite and SNPs have been widely applied in oysters (Hubert and Hedgecock 2004;Varney et al 2009) and have been used for population genetic studies in the past, these approaches suffer from the fact that they tend to be both time consuming and relatively expensive (Fleury et al 2009;Quilang et al 2007). Furthermore, it has been demonstrated that, high levels of non-amplification and PCR-null alleles are often problems in oysters (Xiao et al 2010;Yu and Guo 2005).…”
Section: Introductionmentioning
confidence: 99%